Histone‐lysine N‐methyltransferase EHMT2 (G9a) inhibition mitigates tumorigenicity in Myc‐driven liver cancer - Dexter Kai Hao Thng; Lissa Hooi; Clarissa Chin Min Toh; Jhin Jieh Lim; Deepa Rajagopalan; Imran Qamar Charles Syariff; Zher Min Tan; Masturah Bte Mohd Abdul Rashid; Lei Zhou; Alfred Wei Chieh Kow; Glenn Kunnath Bonney; Brian Kim Poh Goh; et al. (Molecular Oncology, 2023)
Hepatocellular carcinoma (HCC) is the third deadliest and sixth most common cancer in the world. Histone‐lysine N‐methyltransferase EHMT2 (also known as G9a) is a histone methyltransferase frequently overexpressed in many cancer types, including HCC. We showed that Myc‐driven liver tumours have a unique H3K9 methylation pattern with corresponding G9a overexpression. This phenomenon of increased G9a was further observed in our c‐Myc‐positive HCC patient‐derived xenografts. More importantly, we showed that HCC patients with higher c‐Myc and G9a expression levels portend a poorer survival with lower median survival months. We demonstrated that c‐Myc interacts with G9a in HCC and cooperates to regulate c‐Myc‐dependent gene repression. In addition, G9a stabilises c‐Myc to promote cancer development, contributing to the growth and invasive capacity in HCC. Furthermore, combination therapy between G9a and synthetic‐lethal target of c‐Myc, CDK9, demonstrates strong efficacy in patient‐derived avatars of Myc‐driven HCC. Our work suggests that targeting G9a could prove to be a potential therapeutic avenue for Myc‐driven liver cancer. This will increase our understanding of the underlying epigenetic mechanisms of aggressive tumour initiation and lead to improved therapeutic and diagnostic options for Myc‐driven hepatic tumours.